2021
DOI: 10.1007/s42452-021-04689-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of cutting forces and effect of turning parameters on SiCp/Al 45% vs SiCp/Al 50% metal matrix composites: a comparative study

Abstract: In this study, the proposed experimental and second-order model for the cutting forces were developed through several parameters, including cutting speed, feed rate, depth of cut, and two varying content of SiCp. Cutting force model was developed and optimized through RSM and compared for two different percentages of components SiCp/Al 45% and SiCp/Al 50%. ANOVA is used for Quantitative evaluation, the main effects plot along with the evaluation using different graphs and plots including residual analysis, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Tool wear predominantly occurs on the flank surface, necessitating the prediction of tool wear. Researchers such as Saeed [ 48 ] and Rashid et al [ 49 , 50 ] have employed turning experimental devices and artificial neural networks (ANNs) to predict the lateral wear of the tool. They analyzed the influence of process parameters on tool surface wear.…”
Section: Turning Machining Of Sicp/almentioning
confidence: 99%
“…Tool wear predominantly occurs on the flank surface, necessitating the prediction of tool wear. Researchers such as Saeed [ 48 ] and Rashid et al [ 49 , 50 ] have employed turning experimental devices and artificial neural networks (ANNs) to predict the lateral wear of the tool. They analyzed the influence of process parameters on tool surface wear.…”
Section: Turning Machining Of Sicp/almentioning
confidence: 99%
“…The optimal value of the input parameters given by RSM is 1000 rpm, feed 0.15 mm/rev, and depth of cut 0.3 mm for all three composites. Laghari et al [17] optimized the turning of a composite reinforced with SiC particles. They have found that the percentage of SiC reinforcement has no major effect on the cutting forces; on the other hand, the cutting force is more influenced by the cutting parameters, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology investigates the interaction between several descriptive variables and response variables. The optimal factor and their effect was attained in turning process of aluminium composite using RSM 25 . Quadratic model and optimization was used to evaluate the cutting forces in turning of SiC based Al composite 26 .…”
Section: Introductionmentioning
confidence: 99%